Palestinian Feminist Critique and the Physics of Power: Feminists Between Thought and Practice - Shalhoub-Kevorkian, Nadera (feminists@law, 2014)
Grounded in my own position as a Palestinian feminist born and raised in Haifa, this paper delves into the nature of feminism for Palestinian women in the Jewish settler colonial state by asking three main questions: How does the complex socio-political reality of settler colonialism reflect itself in the lives and status of Palestinian women living in Israel? What kind of critical feminist theorizing is needed from Palestinian feminists in Israel? How can we analyze and confront the racism of the historical silence of the majority of Israeli feminists towards the historical injustice and current violence faced by Palestinian feminists? The paper underlines the importance of widening the critical feminist lens to account for the physics of power and calls for (a) the deconstruction of feminisms that have refused to regard the Nakba as a focal analytical and actual source of feminist theorization and (b) defiance in the face of global, regional, and local amnesia towards the Palestinian right to life in the face of Israel’s necropolitical regime of control.